Comparative Study Between a Customized Bimodal Endoscope and a Benchtop Microscope for Quantitative Tissue Diagnosis - Mehidine, Hussein; Devaux, Bertrand; Varlet, Pascale; Abi Haidar, Darine (Frontiers in Oncology, 2022)
Nowadays, surgical removal remains as the standard method to treat brain tumors. During surgery, the neurosurgeon may encounter difficulties to delimitate tumor boundaries and the infiltrating areas as it has a similar visual appearance to adjacent healthy zones. These infiltrating residuals increase the tumor recurrence risk that decrease the patient post-operation survival time. To help neurosurgeons improving the surgical act by accurately delimitating healthy from cancerous areas, our team is developing an intraoperative multimodal imaging tool. It consists of a two-photon fluorescence fibered endomicroscope that is intended to provide a fast, real-time and reliable diagnosis information. In parallel to the instrumental development, a large optical database is currently under construction in order to characterize healthy and tumor brain tissues with their specific optical signature using multimodal analysis of the endogenous fluorescence. Our previous works shows that this multimodality of analysis could provide a reliable discrimination response between different tissue types based on several optical indicators. Here in, our goal is to show that the two-photon fibered endomicroscope in able to provide, and based on the same approved indicators in the tissue database, the same reliable response which could be used intraoperatively. We compared the spectrally and time-resolved fluorescence signal, generated by our two-photon bimodal endoscope from 46 fresh brain tissue samples, with similar signal provided by a standard reference benchtop multiphoton microscope that has been validated for tissue diagnosis. Higher excitation efficiency and collection ability of endogenous fluorescence signal were shown for the endoscope setup. Similar molecular ratios and fluorescence lifetime distributions were extracted from the two-compared setups. Spectral discrimination ability of the bimodal endoscope was validated. As a preliminary step before tackling the multimodality, the ability of the developed bimodal fibred endoscope, to excite and to collect efficiently as well as to provide a fast exploitable high quality signal that is reliable to discriminate different types of human brain tissues was validated.